HAK MASYARAKAT UNTUK MEMPEROLEH KEPASTIAN HUKUM TERKAIT PENCEMARAN LINGKUNGAN - Runtunuwu, Yoan B.; Lasube, Yunarti M.; Manangkot, Alya Rahel; Kaawoan, Debora Stevani; Manganang, Chessy Avril (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
This study aims to analyze the legal certainty of citizens’ rights concerning environmental pollution in Indonesia within the framework of national law and its enforcement practices. The research is motivated by the increasing number of pollution cases and the limited effectiveness of legal protection for affected communities, despite Indonesia’s environmental law framework having adopted the polluter pays, precautionary, and strict liability principles. The study employs a normative juridical method using statutory, case, and conceptual approaches. Primary legal materials include the 1945 Constitution, Law No. 32 of 2009, Government Regulation No. 22 of 2021, and Supreme Court Regulation No. 1 of 2023, all analyzed qualitatively and descriptively through systematic and teleological interpretation. The findings indicate that environmental law enforcement in Indonesia remains dominated by administrative actions (61%), while civil and criminal avenues show low effectiveness due to weak scientific evidence, poor interagency coordination, and limited investigative capacity. The implementation of risk-based licensing and alternative dispute resolution mechanisms, such as online dispute resolution, represents a positive innovation; however, their application remains uneven across sectors and regions. The lack of public participation and transparency in environmental data exacerbates legal uncertainty and weakens both governmental and corporate accountability. This study highlights the need to integrate national legal norms, international principles, and digital technology to strengthen the effectiveness of environmental law enforcement. The findings imply the importance of institutional reform, improved access to justice, and the acceleration of legal modernization toward an equitable and sustainable environmental governance system.